2019
DOI: 10.7150/jca.27399
|View full text |Cite
|
Sign up to set email alerts
|

Log Odds Could Better Predict Survival in Muscle-Invasive Bladder Cancer Patients Compared with pN and Lymph Node Ratio

Abstract: Background: The aim of this study was to assess the prognostic value of lymph node-associated variables, pN, lymph node ratio (LNR) and log odds (LODDS), in patients with bladder cancer.Methods: In the discovery cohort, 3358 patients with muscle-invasive bladder cancer (MIBC) and treated with radical cystectomy were identified from the Surveillance, Epidemiology, and End Results (SEER) database. A total of 173 patients with MIBC who underwent radical cystectomy at Shanghai Cancer Center between 2010 and 2013 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…LNR, the ratio of positive lymph node counts among the total regional lymph nodes examined in the surgery, has been shown to have prognostic value in various cancers, including lung, 29 , 30 bladder, 31 renal, 32 breast, 33 , 34 colorectal, 16 and gastric 15 cancers. However, its prognostic role in testicular germ cell tumors remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…LNR, the ratio of positive lymph node counts among the total regional lymph nodes examined in the surgery, has been shown to have prognostic value in various cancers, including lung, 29 , 30 bladder, 31 renal, 32 breast, 33 , 34 colorectal, 16 and gastric 15 cancers. However, its prognostic role in testicular germ cell tumors remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Leliveld et al reported that pathological TNM stage and age were independent prognosis factors for patients with MIBC who underwent radical cystectomy (20). Jin S et al analyzed lymph node-associated variables [pathological N stage (pN), lymph node ratio (LNR) and log odds (LODDDS)] in the patients with MIBC and found c-index that predicted the survival was 0.6769 (pN), 0.6794 (pN+ LNR), and 0.6855 (pN+LNR+LODDDS) (21). Mitra et al established clinical and genomic classifiers and the c-index was up to 0.73 (18).…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node dissection provides accurate node staging and predictive information for oncologic outcomes except for the tumor stage and grade. In addition, several parameters, based on the lymph node status including positive node count, lymph node density, and log odds, were proposed as prognostic factors for BCa patients (Fransen van de Putte et al, 2015;Masson-Lecomte et al, 2013;Lee et al, 2012;Jin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%